Avaliação da satisfação de pessoas com hipertensão arterial usuárias dos serviços da atenção primária à saúde - Rêgo, Anderson da Silva (2017)
Systemic arterial hypertension is a chronic morbidity, of high prevalence in Brazil and in the world. With a multifactorial origin, it is a great challenge for public health policies. In this regard, knowing the impact of care provided by professionals in the context of Primary Health Care is important. For this purpose, this study aimed to evaluate the satisfaction of people with hypertension who are users of primary health care services. Cross-sectional, quantitative study, with 417 people undergoing treatment of arterial hypertension, accompanied by the Family Health Strategy of 34 Basic Health Units of the municipality, located in the northwest region of the state of Paraná. The data were collected between February and June 2016, through an interview, using an instrument adapted and validated. The instrument addresses essential attributes and derivatives of Primary Health Care, such as access, accessibility, adherence/attachment, coordination, services, community orientation, family orientation and cultural competence. For the treatment of the variables, descriptive and inferential statistical analysis (analysis of variance, multiple logistic regression model) was used, considering p<0.05 as significant. It was possible to observe that the majority of people were ≥ 70 years old (31.9%), female (67.9%), with elementary school (61.1%), white (62.3% %) and belonging to the economic classification C (43.9%). More than half of the interviewees had adequately controlled blood pressure (53.7%) and adequate regular monitoring (62.8%) in the Family Health Strategy. The results showed the strengths and weaknesses of Primary Health Care in the services provided to people under treatment of hypertension; the access dimension (3.92 ± 0.89) was the best evaluated, classified as satisfactory by more than half of the respondents. Community orientation (3.37 ± 1.34) was the domain with regular evaluation. People with uncontrolled blood pressure are more likely to assess the cast of services and coordination as regular and unsatisfactory. Economic accessibility was the best indicator evaluated. The regular evaluation of the services characteristic of geographical (OD: 1.46, 95%CI: 1.27-1.78) and organizational accessibility (OD: 1.96; 95% CI: 1.23-3.10) is significantly associated to the inadequate follow-up of these users in the Family Health Strategy. People with inadequate follow-up evaluate the low ratio between professional/patient (OD: 2.43; 95%CI: 1.13-5.22) as regular and those with inadequate blood pressure control assess the orientation of the medication in use as unsatisfactory (OD: 1.87, 95%CI: 1.08-3.28). The lack of guidelines and dialogue between professionals and users leads to inadequate pressure control and monitoring of people with arterial hypertension. The services offered present geographical and organizational barriers, and there is a need to reorganize the work process of health professionals, as well as to increase guidelines and health education for the participants of this study.